A coordinated power quality improvement control strategy for AC/DC hybrid distribution networks based on three-phase four-leg flexible interconnection converter - Qihui Feng; Jikai Li; Junchao Zhou; Yutao Xu; QingLian He; Yuan Gao (Frontiers in Energy Research)
In this paper, A coordinated power quality improvement control strategy for three-phase four-Leg flexible interconnection converter (3P4L-FIC) based AC/DC hybrid distribution networks is proposed, which can address three-phase unbalance issues in AC area and double frequency ripple issue in DC area simultaneously without extra components. Firstly, for the problems of three-phase load unbalance in the AC station area, the split-phase power decoupling control based power quality optimization is delivered for 3P4L-FIC based hybrid distribution networks. Secondly, the doubling frequency pulsation mechanism of DC bus voltage during three-phase unbalanced compensation conditions is analyzed in detail, and a DC voltage doubling frequency ripple migration scheme based on hybrid proportional-integral and resonant controller (PI-R) is proposed. Finally, the 3P4L-FIC based low-voltage multi-distribution area simulation model constructed by Matlab/Simulink is verified, and the results show that the three-phase imbalance of the low-voltage AC line is completely compensated, and the double-frequency ripple of the DC bus voltage is greatly reduced, which realizes the synergistic enhancement of the power quality of the AC-DC distribution area.